Geophysical characterisation of meta-sedimentary interbeded rock for geotechnical works / Haryati Awang - Awang, Haryati (2010)
This research focuses on the resistivity measurement in ground investigation as one of the geophysical methods for geotechnical assessment. The area of study is limited to the ground of interbedded meta-sedimentary rocks mass of quartzite and phyllite that varies in weathering grades. The goals of this research are to study the subsurface profile layers particularly in meta-sedimentary rock formation. This includes characterising the ground material with respect to the geophysical characteristics and geotechnical engineering parameters with the intention to establish correlations between the georesistivity and rock properties, especially for strength properties. Another goal is to develop a database of the geo-resistivity index of meta-sedimentary rocks with respect to the degree of weathering. In order to achieve the objectives, engineering rock mass and geo-resistivity field studies were performed at selected sites that were located in Puncak Alam area. Geo-resistivity field measurements were carried out using multiple electrodes arrangement where 41 electrodes were laid in equal distance. The laboratory tests were conducted on rock material samples to determine the geo-resistivity and engineering properties. The technique of geo-resistivity test in the laboratory was developed where the method used AC current as power source. By clamping the samples in an innovated holder with a cell pressure of 10 kPa, the resistance was measured using impedance analyser (LCR meter) at a frequency of 500 kHz. The engineering properties of the material were determined using the methods that were proposed by BS 5930 and 1SRM (1981). The findings of field measurements showed a good agreement between geo-resistivity profiles and the actual profiles of rock masses. On the other hand the georesistivity indexes of rock mass and material are in tolerable ranges.